Penggunaan Bahan Ajar Berbasis RME untuk Meningkatkan Penalaran dan Numerasi Matematis Materi Pecahan di Sekolah Dasar - Tri Rezeki, Irma Setiawati; Wiryanto, Wiryanto; Siswono, Tatag Yuli Eko (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to look at the use of RME teaching materials on fraction materials to improve mathematical reasoning and numeracy of elementary school students. The method in preparing this article uses the literature review method, this research presents the results of a search for articles on the use of RME teaching materials in elementary schools. The results of this study indicate that ten articles have been reviewed that RME-based teaching materials are a very effective tool for improving mathematics learning, especially in fraction materials in elementary schools. By combining contextual approaches, concrete media, and technology, RME provides a deeper and more meaningful learning experience for students. Conclusion, Through the RME approach, students can relate mathematical concepts to their daily experiences, thus making learning more relevant and interesting.   Keywords: Teaching Materials, RME, Mathematics